DIREKTORAT JENDERAL PAJAK SEBAGAI PENEGAK HUKUM TRANSFORMATIF DI INDONESIA - Krisnapati, Bayu (Scientax, 2019)
Directorate General of Taxes (DGT) is a government institution that half of the authority is judicative because the DGT is able to collect revenue by using enforcement to taxpayers. The DGT has judicative characteristic so that the DGT must be abreast with the other law enforcement institution in Indonesia law system. In this case, the writer used the term of Transformative Law Enforcement (TLE). Act number 9/2017 gives new duty and power for the DGT so that it strengthen DGT position as a TLE. This research focuses on DGT role as a TLE until the existence of the DGT can be recognized in public law system and is purposed for the DGT to have specific law that manage the DGT. This research use normative judicatory approach method and qualitative descriptive with secondary data. The conclusion is that Act number 9/2017 gives new duty and power for the DGT as TLE to have unimpeded access of financial information from financial service institution and another entity in order to increase taxpayer compliance eventhough it might cause conflict of interest with Bank Indonesia as the central bank and the highest authority of all banks in Indonesia.